Advanced Therapeutic Options for Treatment of Metastatic Castration Resistant Prostatic Adenocarcinoma - Naseer, Faiza; Ahmad, Tahir; Kousar, Kousain; Anjum, Sadia (Frontiers in Pharmacology, 2021)
The initial stage prostatic adenocarcinoma (PaC) has been treated with surgery and radiation therapy but advanced stages need systemic novel treatment. Later 2010, multiple advanced therapeutic novelties have been introduced to improve survival and reduce morbidity and mortality in different randomized clinical trials. Several therapeutic moieties have been approved with substantial global survival assistances in even advanced stages of metastatic castration resistant prostatic adenocarcinoma (mCRPC) including various available chemotherapeutic options, hormonal therapies (abiraterone, enzalutamide), immunotherapeutic & bone modifying agents and gene therapy approaches including Crispr/Cas9 mediation, oncolytic viruses, suicidal genes and micro-RNA based antitumor therapy. The mCRPC microenvironment is characterized by raised prostate specific antigen (PSA) levels, which ultimately triggering the androgen receptor (AR) and its dependent pathways. These recently developed moieties targeting these kind of receptors and hindering the steroidogenic enzymes, which play important role in the production of testosterone (T) and dihydrotestosterone (DHT) in the body. So, seems to be an attractive strategy for acute and chronic stages of PaC and mCRPC treatment by overcoming the resistance mechanisms. These advanced therapeutic novelties also target AR-independent oncogenic signaling pathways by focusing on DNA damage repair (DDR) pathways and their mechanisms.